EFEKTIVITAS PENERAPAN STRATEGI SQ3R DALAM MEMAHAMI TEKS LAPORAN HASIL OBSERVASI PADA SISWA KELAS X SMK PLUS ULUMUL QURAN KUNIR TAHUN PELAJARAN 2019/2020 - Maulana, Irpan (STKIP Subang, 2019)
The ability of students to read comprehension is relatively low, especially in understanding the reading text of the report of observations, so we need a learning innovation that can improve students' ability to read comprehension through the application of the SQ3R strategy. The formulation of the problem in this study are (1) How is the ability to read text comprehension reports on students' observations? (2) What is the ability to read understanding text reports of students' observations after using the SQ3R strategy? (3) Is the application of the SQ3R learning strategy effective in learning to read the text of the observation report? The purpose of this study is (1) to describe the ability of students to read the understanding of the text of the observation report. (2) describe the ability of students to read the text of the observation report after using SQ3R. (3) describe the effectiveness of the use of SQ3R in learning to read the text of the observation report. This study uses the Pre Experiment research method with the One-Group Pretest-Postest design. The results of the study showed that there was an increase in the ability to read comprehension in the text of the student's observation report. This is indicated by an increase in the average reading comprehension value of 15.98 from the average results before the implementation of the SQ3R learning strategy by 55.83 and after the implementation of the SQ3R strategy by 71.81. So that the SQ3R strategy is effectively applied to the learning of reading comprehension of the observation report text.